Long‐term outcomes and mutation profiling of patients with mantle cell lymphoma (MCL) who discontinued ibrutinib. (2nd September 2018) - Jain, Preetesh; Kanagal‐Shamanna, Rashmi; Zhang, Shaojun; Ahmed, Makhdum; Ghorab, Ahmad; Zhang, Liang; Ok, Chi Young; Li, Shaoying; Hagemeister, Frederick; Zeng, Dongfeng; Gong, Tiejun; Chen, Wendy; et al.
Summary: Long term outcomes and mutations in patients with mantle cell lymphoma (MCL) who discontinued ibrutinib have not been described. Using deep targeted next generation sequencing, we performed somatic mutation profiling from 15 MCL patients (including 5 patients with paired samples; before and after progression on ibrutinib). We identified 80 patients with MCL who discontinued ibrutinib therapy for various reasons. Median follow‐up after ibrutinib discontinuation was 38 months. The median duration on ibrutinib was 7·6 months. Forty‐one (51%) patients discontinued ibrutinib due to disease progression/transformation, 20 (25%) for intolerance, 7 (9%) due to patient choice, 5 (6%) for stem cell transplant, 4 (5%) due to second cancers and 3 (4%) other causes. The median survival after ibrutinib was 10 and 6 months for disease progression and transformation, respectively, and 25 months for patients with ibrutinib intolerance. Overall, BTK mutations were observed in 17% patients after progression on ibrutinib. Notably, TP53 alterations were observed after progression in 75% patients. Among the 4 patients with blastoid transformation, 3 (75%) had NSD2 mutations (co‐existing with TP53 ). Ibrutinib‐refractory MCL patients had a short survival. Demonstration of TP53 and NSD2 mutations in patients who developed blastoid transformation and ATM and TP53 mutations in patients who progressed, opens the door for future investigations in ibrutinib‐refractory MCL.